Hubungan Antara Konsep Duâ€™a Nggaâ€™e Sebagai Realitas Tertinggi Suku Ende-Lio Dengan Iman Kristiani - Mathias Jebaru Adon; Siklus Rikardus Depa; Vinsensius Rixnaldi Masut (Universitas Muhammadiyah Surabaya, 2021)
This study aims to explain the concept of Du'a Ngga'e as the ultimate reality of the Ende-Lio tribe, Flores about the Christian faith. The Ende-Lio people believe that before the Catholic Church proclaims their faith in God, they have known and worshiped â€œAllahâ€ as the ultimate reality with the name Du'a Ngga'e. The people of the Ende-Lio tribe believe in Du'a Ngga'e as the origin of all things and the source of human life so that they must be respected and worshiped in the hanga (sacred space). Therefore, the Catholic Church must continue to pay attention to the noble values of local culture by building an equal horizontal dialogue without discrediting one another. The methodology used in this study is a qualitative method by conducting in-depth interviews and literature studies on the two variables. This study found two important things, namely: (1) In the concept of Du'a Ngga'e, the Ende-Lio tribal community already contains the truths of Christian faith in God Almighty. (2) The consequence is that the Church must respect the local culture as an entry point in proclaiming the Christian faith.